2017
DOI: 10.3171/2015.11.jns151177
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in the diagnosis and management of trigeminal neuralgia

Abstract: OBJECTIVE A number of studies have documented inequalities in care and outcomes for a variety of clinical conditions. The authors sought to identify racial and socioeconomic disparities in the diagnosis and treatment of trigeminal neuralgia (TN), as well as the potential underlying reasons for those disparities, which could serve as areas of focus for future quality improvement initiatives. METHODS The medical records of patients with an ICD-9 code of 350.1, signifying a diagnosis of TN, at the Henry Ford Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This is even more problematic when it comes to race. It is well documented, for example, that African Americans with chronic pain are at greater risk of undertreatment [106,107] and invalidation by providers [108,109]. African Americans with chronic pain also report greater pain intensity, distress, and interference with functioning [110,111], especially those who are living in poorer urban areas [112].…”
Section: Limitationsmentioning
confidence: 99%
“…This is even more problematic when it comes to race. It is well documented, for example, that African Americans with chronic pain are at greater risk of undertreatment [106,107] and invalidation by providers [108,109]. African Americans with chronic pain also report greater pain intensity, distress, and interference with functioning [110,111], especially those who are living in poorer urban areas [112].…”
Section: Limitationsmentioning
confidence: 99%
“…Regarding the pathogenesis of TN, it is believed that the trigeminal nerve becomes chronically compressed by abnormal twisted microvessels in the REZ area, resulting in inflammation and demyelination changes in the root of the trigeminal nerve and thus in a “short circuit” of membrane potential and neuropathic pain in the trigeminal nerve distribution area ( 14 ). One study ( 4 ) showed that the size, shape, and structure of the skull varies according to race and sex. Asians, especially women, have a higher incidence of TN and more crowding in the posterior fossa.…”
Section: Discussionmentioning
confidence: 99%
“…By eliminating NVC, microsurgical vascular decompression (MVD) can successfully relieve pain. Several studies have shown that the small space of the posterior cranial fossa is associated with NVC, suggesting a correlation between overcrowding of the posterior cranial fossa and TN (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In our study population, the right side was more affected than the left (13 patients, 68.5% versus 6 patients, 31.5%, respectively). This may be attributed to the anatomical fact that foramen rotundum and foramen ovale are usually narrower on the right side [16,[23][24][25]. The mandibular and/or maxillary branches were equally affected.…”
Section: Discussionmentioning
confidence: 99%